Smart Agricultural System in Greenhouse based on Internet of Things for Lettuce (Lactuca sativa L.) - Grey Mart Bonde; Daniel P.M. Ludong; Meicsy E.I Najoan (Jurnal Teknik Elektro dan Komputer, 2021)
Abstract — Indonesian Agricultural sistem for vegetable still using a conventional method. However, conventional method is having a problem, which is  weather.  Indonesia’s weather condition is going uncertain because the global warming effect. Uncertain weather cause plant’s growth agitated. Greenhouse is one of the human’s innovation to keep and increase plant  growth.  This research using IoT based smart system in greenhouse. Greenhouse was built to create new environment to separated from the outside environment. Sensors are applied to monitor the environment. In greenhouse, writer applied actuator to maintain the environment at the optimal condition. The condition inside greenhouse can be seen  in website. The main purpose of this research are to design, build, and control the IoT-based greenhouse for best condition of lettuce’s growing climate. This research using experimental method on development project. The micro-climate range that the researcher using for this research are at 22-30 Celcius degree for the temperature, 90% for the humidity, and 100 LDR’s scale for  the  light intensity. By applying IoT based smart system inside greenhouse, plant growth can be seen clearly in the website. The condition of the environment can maintain at the optimal contition for the plant growth, with the manual or automatical control. With this device, the plant growth  can maintain at the best condition and it will produce plant that grow at the best condition